Effects on Puberty of Nutrition-Mediated Endocrine Disruptors Employed in Agriculture - Anastasia Konstantina Sakali (MDPI AG, 2021)
Pesticide residues are largely found in daily consumed food because of their extensive use in farming and their long half-life, which prolongs their presence in the environment. Many of these pesticides act as endocrine-disrupting chemicals after pre- or postnatal exposure, significantly affecting, among other things, the time of puberty onset, progression, and completion. In humans, precocious or delayed puberty, and early or delayed sexual maturation, may entail several negative long-term health implications. In this review, we summarize the current evidence on the impact of endocrine-disrupting pesticides upon the timing of the landmarks of female and male puberty in both animals (vaginal opening, first estrus, and balanopreputial separation) and humans (thelarche, menarche, gonadarche). Moreover, we explore the possible mechanisms of action of the reviewed endocrine-disrupting pesticides on the human reproductive system. Access to safe, healthy, and nutritious food is fundamental for the maintenance of health and wellbeing. Eliminating the presence of hazardous chemicals in largely consumed food products may increase their nutritional value and be proven beneficial for overall health. Consequently, understanding the effects of human exposure to hazardous endocrine-disrupting pesticides, and legislating against their circulation, are of major importance for the protection of health in vulnerable populations, such as children and adolescents.